2019
DOI: 10.5194/acp-2019-139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ice core records of biomass burning tracers (levoglucosan, dehydroabietic and vanillic acids) from Aurora Peak in Alaska since 1660s: A new dimension of forest fire activities in the Northern Hemisphere

Abstract: <p><strong>Abstract.</strong> A 180 m long (ca. 274 years) ice core was drilled in the saddle of the Aurora Peak of Alaska (63.52° N; 146.54° W, elevation: 2825 m). The ice core samples were melt, concentrated and then derivatized with N,O-bis-(trimethylsilyl) trifluoroacetamide with 1 % trimethylsilyl chloride and pyridine followed by gas chromatography/mass spectrometry an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Guaiacol is one of the many aromatic compounds emitted by biomass burning, which is a significant source of organics to remote polar regions. [56][57][58][59] To understand what our experimental results mean for the lifetimes of guaiacol in polar snow, we calculated guaiacol photodegradation rate constants for Summit, Greenland under summer solstice sunlight. We used equation with:…”
Section: Environmental Implications and Conclusionmentioning
confidence: 99%
“…Guaiacol is one of the many aromatic compounds emitted by biomass burning, which is a significant source of organics to remote polar regions. [56][57][58][59] To understand what our experimental results mean for the lifetimes of guaiacol in polar snow, we calculated guaiacol photodegradation rate constants for Summit, Greenland under summer solstice sunlight. We used equation with:…”
Section: Environmental Implications and Conclusionmentioning
confidence: 99%
“…Terrestrial higher plants to marine phytoplanktons emitted huge amounts of biogenic VOCs, which are 10 times larger than anthropogenic VOCs on a global scale (Seinfeld and Pandis, 1998). Biogenic and anthropogenic VOCs are oxidized in the atmosphere to result in secondary organic aerosols (SOA), which are further oxidized to diacids, oxoacids, glyoxal, and methylglyoxal via heterogeneous reactions (Talbot et al, 1995;Lim et al, 2005;Volkamer et al, 2009;Kunwar and Kawamura, 2014a,b;Pokhrel et al, 2019). Carlton et al (2006Carlton et al ( , 2007 and Zhu et al (2015) reported that primary organic aerosols (POA) are emitted from plants, fungal spore, fossil fuel combustion, biomass burning, and soil particles, whereas SOA are photochemically produced by heterogeneous oxidations of biogenic and anthropogenic VOCs (Surratt et al, 2010;Ho et al, 2010;Kundu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%